Sitagliptin and pioglitazone provide complementary effects on postprandial glucose and pancreatic islet cell function. Issue 12 (19th July 2013) - Alba, M.; Ahrén, B.; Inzucchi, S. E.; Guan, Y.; Mallick, M.; Xu, L.; O'Neill, E. A.; Williams‐Herman, D. E.; Kaufman, K. D.; Goldstein, B. J.
Abstract : Aims: The effects of sitagliptin and pioglitazone, alone and in combination, on α ‐ and β‐cell function were assessed in patients with type 2 diabetes. Methods: Following a 6‐week diet/exercise period, 211 patients with HbA1c of 6.5–9.0% and fasting plasma glucose of 7.2–14.4 mmol/l were randomized (1 :1 :1 : 1) to sitagliptin, pioglitazone, sitagliptin + pioglitazone or placebo. At baseline and after 12 weeks, patients were given a mixed meal followed by frequent blood sampling for measurements of glucose, insulin, C‐peptide and glucagon. Results: After 12 weeks, 5‐h glucose total area under the curve (AUC) decreased in all active treatments versus placebo; reduction with sitagliptin + pioglitazone was greater versus either monotherapy. The 5‐h insulin total AUC increased with sitagliptin versus all other treatments and increased with sitagliptin + pioglitazone versus pioglitazone. The 3‐h glucagon AUC decreased with sitagliptin versus placebo and decreased with sitagliptin + pioglitazone versus pioglitazone or placebo. Φs, a measure of dynamic β‐cell responsiveness to above‐basal glucose concentrations, increased with either monotherapy versus placebo and increased with sitagliptin + pioglitazone versus either monotherapy. The insulin sensitivity index (ISI), a composite index of insulin sensitivity, improved with pioglitazone and sitagliptin + pioglitazone versus placebo. The disposition index, a measure of the relationship between β‐cell function and insulin sensitivity, improved with all active treatments versus placebo. Conclusions: Sitagliptin and pioglitazone enhanced β‐cell function (increasing postmeal Φs ), and sitagliptin improved α ‐cell function (decreasing postmeal glucagon) after 12 weeks in patients with type 2 diabetes. Through these complementary mechanisms of action, the combination of sitagliptin and pioglitazone reduced postmeal glucose more than either treatment alone.